Hypoxia and the Circulation - Roach, Robert; Wagner, Peter D.; Hackett, Peter; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2007)
The hypoxia volumes will focus on cutting edge research at the interface of hypoxia and biomedicine. Hypoxia is a constant threat to the human body and its vital organs throughout life. There are many situations in which the threat is heightened in health and disease, but mechanisms have evolved to lessen its detrimental effects. The International Hypoxia Symposia was founded to enable scientists, clinicians, physiologists, immunologists, mountaineers and other interested individuals to share their experiences of the situations associated with oxygen lack and the adaptations that allow us to survive. The mission of the International Hypoxia Symposia is to present cutting edge, sophisticated research at the very highest levels into the many effects of hypoxia on humans and animals in health and disease.
Risk of Cardiovascular Events During Mountain Activities -- Biventricular Function at High Altitude: Implications for Regulation of Stroke Volume in Chronic Hypoxia -- Control of Coronary Blood Flow During Hypoxemia -- Metabolic Consequences Of Intermittent Hypoxia -- Intermittent Hypoxia and Cognitive Function: Implications from Chronic Animal Models -- Vascular Consequences of Intermittent Hypoxia -- Angiotensin-Induced Hypoxia in the Kidney: Functional and Structural Changes of the Renal Circulation -- Role of Reactive Oxygen Species in Chronic Hypoxia-Induced Pulmonary Hypertension and Vascular Remodeling -- Hypoxia and Placental Remodelling -- Epithelial Sodium Channels in the Adult Lung – Important Modulators of Pulmonary Health and Disease -- Lung Interstitial Pressure and Structure in Acute Hypoxia -- Hypoxic Inhibition of Alveolar Fluid Reabsorption -- Regulation and Role of Neuroglobin and Cytoglobin Under Hypoxia -- Molecular Insights into the Functional Role of Myoglobin -- GenetiC Mechanisms Underlying Regulation of Hemoglobin Mass -- Control of the Respiratory Pattern in Insects -- Effects of Insect Body Size on Tracheal Structure and Function -- The Role of Hif-1 1 in Hypoxic Response in the Skeletal Muscle -- Gene Expression in Working Skeletal Muscle -- The Limits of Human Endurance: What is the Greatest Endurance Performance of All Time? Which Factors Regulate Performance at Extreme Altitude? -- Jim Milledge Hypoxia Honoree 2007 -- Exploring Mountain Medicine and Physiology -- Carlos Monge Cassinelli: A Portrait.
Keywords: Medicine; Human physiology; Immunology; Neurosciences; Biomedicine, general; Human Physiology; Immunology; Neurosciences